Reversal of endoscopic sleeve gastroplasty and conversion to sleeve gastrectomy – Two case reports. (2020) - Cheng, Qiuye; Tree, Kevin; Edye, Michael; Devadas, Michael
Highlights: ESG conversion to sleeve gastrectomy is feasible and for the most part, uncomplicated. Conversion of ESG to LSG can be performed safely through a combined endoscopic-laparoscopic technique. Return to original stomach anatomy and a meticulous approach in removing most, if not all of the ESG hardware is required for success. Abstract: Introduction: With the advent of more minimally invasive procedures like endoscopic sleeve gastroplasty (ESG) for weight loss and metabolic disorders, we are seeing more cases of patients presenting with sub-optimal results for consideration of alternative weight loss surgery. The report aims to describe our experience in converting ESG to laparoscopic sleeve gastrectomy and highlight our suggested technique, challenges and pitfalls. Presentation of cases: We described two bariatrics cases detailing our findings on initial endoscopy along with methods used to reverse ESG hardware, followed by issues encountered during sleeve gastrectomy 1 month later. Case 1 being of a 33 year old female (BMI – 50.7) with previous laparoscopic band removal and 2 ESG attempts, while case 2 is a 31 year old female (BMI 44.6) with previously failed gastric balloon and ESG. Discussion: ESG reversal was performed without difficulty via endoscopy with visible sutures cut and hardware removed with snares. In both cases, the stomach was easily endoscopically distensible. During sleeve gastrectomy, extra-gastric adhesions along with more gastro-gastric sutures were encountered in case 1. In case 2, ESG hardware was noted on the external surface of stomach with misfiring of 3rd stapler reload during sleeve gastrectomy likely related to unidentified retained hardware. No post-operative complications occurred in either of the cases with adequate weight loss on one month follow up. Conclusion: In our experience, ESG conversion to sleeve gastrectomy is feasible and for the most part, uncomplicated. In our case series, we described a two staged approach to conversion although a single staged conversion is theoretically feasible.